REM Sleep Rebound as an Adaptive Response to Stressful Situations - Suchecki, Deborah; Tiba, Paula A.; Machado, Ricardo B. (Frontiers in Neurology, 2012)
Stress and sleep are related to each other in a bidirectional way. If on one hand poor or inadequate sleep exacerbates emotional, behavioral and stress-related responses, on the other hand acute stress induces sleep rebound, most likely as a form to cope with the adverse stimuli. Chronic stress, conversely, has been claimed to be one of the triggering factors of emotional-related sleep disorders, such as insomnia, depressive- and anxiety-disorders. These outcomes are dependent on individual psychobiological characteristics, which confer more complexity to the stress-sleep relationship. Its neurobiology has only recently begun to be explored, through animal models, which are also valuable for the development of potential therapeutic agents and preventive actions. This review seeks to present data on the effects of stress on sleep and the different approaches used to study this relationship as well as possible neurobiological underpinnings and mechanisms involved. The results of numerous studies in humans and animals indicate that increased sleep, especially the REM phase, following a stressful situation is an important adaptive behavior for recovery. However, this endogenous advantage appears to be impaired in human beings and rodent strains that exhibit high levels of anxiety and anxiety-like behavior.